The Potential of Online Workouts for Fitness Trainers - Bartha, Éva Judit; Szalánczi, Zoltán (International Journal of Engineering and Management Sciences, 2021)
The importance of physical activity for both physical and mental health is unquestionable. For leisure athletes, fitness clubs can be considered as popular facilities for everyday workouts. Classes run by qualified trainers, whether individual or group workouts, are very popular. In line with the worldwide trend, there is a growing expectation for fitness workouts to be reachable as simple as possible, in as many forms as possible, regardless of the location. The aim of our study is therefore to map the prevalence of online training among trainers working in the fitness sector. There is a significant demand for such workouts, even if it cannot completely replace hours of personal presence. In addition, as well as for target groups who want to find a form of exercise that can be performed anywhere, anytime, the online space provides an ideal opportunity to practice regular physical activity, as well as a good opportunity for coaches to expand their clientele and services.